Young children as playwrights and their participation in classroom peer culture of sociodramatic play. (September 2020) - Stagg Peterson, Shelley; Jang, Soon Young; Tjandra, Christina
In this study, analysis of video recordings of 5-year-old children's use of language and nonverbal modes of communication (e.g. gaze, action, gesture, and proximity) is used to examine how children contribute to sociodramatic play narratives and participate in the classroom peer culture. In their dramatic play at a restaurant play center and at a grocery store dramatic play center, eight focus children took up narrative playwright roles, where they contributed to the narrative of the dramatic play, mainly by expressing their own needs and by making connections or providing information to their peers. Children took up intervening playwright roles, in which they changed the direction of the narrative, changed or suggested a change of role, or assigned a new role to an object, most frequently by expressing desires or by providing new information. Dramatic play provided an authentic context for the children to try out various social strategies and to observe how others responded to their efforts, in order to position themselves in desirable ways within the classroom social network. Children took up powerful roles through frequency of participation and through directing others' actions and maintaining the use of desired objects when continuing the play narrative by taking up narrative playwright roles. In addition, they used humor and made imaginative suggestions for roles and plots when taking up intervening playwright roles where they introduced new characters, roles for objects, and plots. Our research provides examples of peers teaching each other in dramatic play through the responses they give to each other and through modeling social approaches that allow them to fulfill desired social purposes and take up powerful social roles in the peer network.